The MicroRNA319d/TCP10 Node Regulates the Common Bean – Rhizobia Nitrogen-Fixing Symbiosis - Martín-Rodríguez, José Á.; Leija, Alfonso; Formey, Damien; Hernández, Georgina (Frontiers in Plant Science, 2018)
Micro-RNAs from legume plants are emerging as relevant regulators of the rhizobia nitrogen-fixing symbiosis. In this work we functionally characterized the role of the node conformed by micro-RNA319 (miR319) - TEOSINTE BRANCHED/CYCLOIDEA/PCF (TCP) transcription factor in the common bean (Phaseolus vulgaris) - Rhizobium tropici symbiosis. The miR319d, one of nine miR319 isoforms from common bean, was highly expressed in root and nodules from inoculated plants as compared to roots from fertilized plants. The miR319d targets TCP10 (Phvul.005G067950), identified by degradome analysis, whose expression showed a negative correlation with miR319d expression. The phenotypic analysis of R. tropici-inoculated composite plants with transgenic roots/nodules overexpressing or silencing the function of miR319d demonstrated the relevant role of the miR319d/TCP10 node in the common bean rhizobia symbiosis. Increased miR319d resulted in reduced root length/width ratio, increased rhizobial infection evidenced by more deformed root hairs and infection threads, and decreased nodule formation and nitrogenase activity per plant. In addition, these plants with lower TCP10 levels showed decreased expression level of the jasmonic acid (JA) biosynthetic gene: LOX2. The transcription of LOX2 by TCPs has been demonstrated for Arabidopsis and in several plants LOX2 level and JA content have been associate with TCP levels. On this basis, we propose that in roots/nodules of inoculated common bean plants TCP10 could be the transcriptional regulator of LOX2 and the miR319d/TCP10 node could affect nodulation through JA signaling. However, given the complexity of nodulation, the participation of other signaling pathways in the phenotypes observed cannot be ruled out.